KAJIAN PARTISIPASI MASYARAKAT DALAM PENGEMBANGAN DESTINASI WISATA DI KABUPATEN LOMBOK UTARA - I Putu Gede; Syech Idrus; Lalu Yulendra (Seminar Ilmiah Nasional Teknologi, Sains, dan Sosial Humaniora (SINTESA), 2018)
ABSTRACTLombok tourism development shows an increase in the number of significant tourist visits until August 2018 totaling 2,469,026 wisnu and foreign tourists. The increase in visits has not been offset by the participation of local communities in the development of tourist destinations in North Lombok Regency. The purpose of this study is (1) to examine the forms of past local community participation in supporting the development of Gumantar North Lombok tourist destinations; (2) to study the current forms of community participation of local and village governments in supporting the development of Gumantar North Lombok tourist destinations; (3) to study the future forms of Community Participation and provide recommendations for involving the community in participating in the development of tourist destinations in the Gumantar tourism village of North Lombok. The research method used is a collaboration between qualitative and quantitative approaches using data collection techniques through direct observation (observation), in-depth interviews (depth interviews), data processing using qualitative descriptive analysis presented in narrative form. The results of the study show that differences in community participation from the past tend to be very simple participatory, obedient to the rules of custom / awig law, ethical and polite in expressing opinions so that past participation is very strong in the development of tourist destinations. The participation of today's society still shows adherence and adheres to the rules of customary law / awig, ethics and courtesy in expressing opinions is more critical because the influence of information technology that has penetrated into the village and the role of the government began to show its existence, so that the participation of today's society tends to experience weakening in the development of tourist destinations. While future community participation is suspected to show a more apathetic and critical tendency because of an increase in better levels of public education, a consumptive lifestyle, modernization of facilities, infrastructure available in the village, the dominant role of the government in developing tourist destinations and community empowermentKey words: Participation, community, tourist destination